2020
DOI: 10.1016/j.psj.2020.08.067
|View full text |Cite|
|
Sign up to set email alerts
|

Chondronecrosis with osteomyelitis in broilers: further defining a bacterial challenge model using standard litter flooring and protection with probiotics

Abstract: This report demonstrates that high levels of lameness can be induced by a limited bacterial challenge in drinking water for birds raised on litter flooring, comparable with lameness induced by the gold standard for inducing lameness, growth on suspended wire flooring. The bacterium used in the challenge was cultured from lesions in birds induced for bacterial chondronecrosis with osteomyelitis ( BCO ) in the wire-flooring model so the epidemiology appears similar. The litter-flooring mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…These data extend the range of products that can be used to reduce BCO lameness, highlight the importance of organic trace minerals in improving animal well-being, and provide further validation of the 2 models we have developed to investigate treatments and management strategies for reducing BCO lameness in broiler operations. Our recent work demonstrating that certain probiotics can also reduce BCO lameness ( Alrubaye et al., 2020 ) strongly supports investigations pairing probiotics with Availa-ZMC to determine whether the protective effects are overlapping, additive, or synergistic. The litter flooring model with the bacterial challenge provides an excellent system for evaluation of these interactions.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…These data extend the range of products that can be used to reduce BCO lameness, highlight the importance of organic trace minerals in improving animal well-being, and provide further validation of the 2 models we have developed to investigate treatments and management strategies for reducing BCO lameness in broiler operations. Our recent work demonstrating that certain probiotics can also reduce BCO lameness ( Alrubaye et al., 2020 ) strongly supports investigations pairing probiotics with Availa-ZMC to determine whether the protective effects are overlapping, additive, or synergistic. The litter flooring model with the bacterial challenge provides an excellent system for evaluation of these interactions.…”
Section: Discussionsupporting
confidence: 69%
“…In our previous research publications, we had reported that S. agnetis 908 can induce 80 to 90% lameness when administered to birds raised on wire flooring ( Al-Rubaye et al., 2015 ; Al-Rubaye et al., 2017 ). We also demonstrated that S. agnetis 908 can induce 50 to 80% lameness when administered in drinking water to birds raised on litter flooring ( Alrubaye et al., 2020 ). Furthermore, the lameness can be transmitted from the birds challenged with bacteria to unchallenged birds within the same broiler house.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations